2008
DOI: 10.1016/j.eeh.2007.07.001
|View full text |Cite
|
Sign up to set email alerts
|

From home to hospital: The evolution of childbirth in the United States, 1928–1940

Abstract: This paper examines the shift in childbirth from home to hospital that occurred in the United States in the early twentieth century. Using a panel of city-level data over the period 1927-1940, we examine the shift of childbirth from home to hospital and analyze the impact of medical care on maternal mortality. Results suggest that increased operative intervention on the part of physicians and a resultant greater risk of infection increased maternal mortality prior to the introduction of sulfa drugs in 1937. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 20 publications
1
43
0
Order By: Relevance
“…Further information can be found at http://www.ssa.gov/history/ childb1.html. 15 Thomasson and Treber (2008) showed that the hospitalization of childbirth had a positive effect on maternal mortality between 1927 and 1937 in the United States. Loudon (1992a) showed that in England, than two-thirds of all maternal deaths were preventable and that many physicians were found to lack the most basic obstetric knowledge (CDC (1999)).…”
Section: Historical Backgroundmentioning
confidence: 99%
“…Further information can be found at http://www.ssa.gov/history/ childb1.html. 15 Thomasson and Treber (2008) showed that the hospitalization of childbirth had a positive effect on maternal mortality between 1927 and 1937 in the United States. Loudon (1992a) showed that in England, than two-thirds of all maternal deaths were preventable and that many physicians were found to lack the most basic obstetric knowledge (CDC (1999)).…”
Section: Historical Backgroundmentioning
confidence: 99%
“…In the other cases, MMR improvements increased life expectancy by much less. For example, MMR fell dramatically in the United States around 1936 after the introduction of sulfa drugs (Thomasson and Treber 2004). However, life table calculations suggest that the elimination of maternal mortality in the United States increased female life expectancy by less than 0.5 years at most (Retherford 1972).…”
Section: Introductionmentioning
confidence: 99%
“…They are also robust to controlling for maternal mortality, which declined sharply after 1937 as a result of the sulfa drug revolution (Thomasson and Treber, 2008;Jayachandran et al, 2010). Using a more flexible specification that allows for differential impacts by age of exposure, we do not find any noteworthy long run health or socioeconomic gains from reductions in pneumonia for cohorts born before 1937, who were at least a year old when sulfa drugs were first introduced.…”
Section: Introductionmentioning
confidence: 74%
“…Furthermore, maternal mortality rates fell sharply in 1937 (Thomasson and Treber, 2008;Jayachandran et al, 2010). To account for this we control for maternal mortality rates, allowing their impact to break in 1937 (i.e.…”
Section: Diseases Not Treatable By Sulfa Drugsmentioning
confidence: 99%